Holes - Sachar, Louis, 1954- (New York : Farrar, Straus and Giroux, 2000)
As further evidence of his family's bad fortune which they attribute to a curse on a distant relative, Stanley Yelnats is sent to a hellish correctional camp in the Texas desert where he finds his first real friend, a treasure, and a new sense of himself.
"Frances Foster books."
G4
Newbery Medal, 1999.
Keywords: Juvenile delinquency -- Fiction; Homeless persons -- Fiction; Friendship -- Fiction; Buried treasure -- Fiction